Determination of optimum row spacing for better seed yield and yield contributing characters of advanced mustard (Brassica napus L.) mutants in Bangladesh - Islam, MS; Ali, MI; Hossain, MS; Chowdhury, SMA (Bangladesh Journal of Nuclear Agriculture, 2023)
A field experiment was conducted at BINA substations, Rangpur and Magura in 2018-19 to evaluate the different row spacing on the yield and yield contributing characteristics of advance mustard lines RM-03, RM-07, RM-10 along with one check variety BARI sarisha-15 during Rabi season. BARI sarisha-15 was irradiated with 700 Gy Cobalt 60 (60Co) Gamma source and advanced mutant lines M6 generation of mustard mutant (RM-03, RM-07, RM-10) were evaluated along with the check variety BARI sarisha-15 using four different row spacings viz. 20cm, 25cm, 30cm and 35cm. The experiment was laid out in split-split plot design with three replications. Among the advance lines, RM-03 produced the highest seed yield (1.60 t ha-1) followed by RM-10 (1.50 t ha-1). Among different line spacing, 20cm showed highest seed yield (1.66 t ha-1). The interaction of mutant/variety and location revealed that the yield of RM-10 was the highest (1.54 t ha-1) at Rangpur. The interaction effect of line spacing and location showed that 25cm line spacing produced the maximum seed yield (1.68 t ha-1) in Magura followed by 20 cm (1.64 t ha-1) in Rangpur. The interaction effect of mutant and line spacing showed that mutant line RM-03 at 20 cm produced maximum seed yield (1.68 t ha-1) in Rangpur. The interaction effect of mutant/variety, line spacing and location showed that RM-10 produced the highest seed yield (1.73 t ha-1) at 20cm line spacing in Rangpur followed by RM-07 (1.66 t ha-1) at same spacing. Bangladesh J. Nuclear Agric, 37(1): 41-50, 2023